THE IMPORTANCE OF PSYCHOPEDAGOGUES IN HIGHER EDUCATION ROUTINES - da Silva Milhomem, Poliana (Revista Gênero e Interdisciplinaridade, 2025)
This paper aims to establish the importance that psychopedagogues can have in the learning process of students in higher education. Highlighting some of the main characteristics and procedures that underlie how psychopedagogy and its professionals become a relevant basis for consolidating learning in higher education. The general objective of the research is to describe the importance of the psychopedagogue in the higher education environment. As for the specific objectives, these are: to present the main aspects of the psychopedagogue; to highlight the characteristics of psychopedagogy in higher education; to analyze the role developed by the psychopedagogue in higher education institutions. To consolidate the information presented, a literature review will be developed, highlighting some of the main concepts and analyses of renowned authors in the educational field. It can be concluded that psychopedagogy is relevant in the routine of students enrolled in higher education, working and presenting tools that can be applied for a positive performance of students in terms of knowledge.